Parenting Style and Suicidal Behavior: A Focused Review - S. M. Yasir Arafat; Vikas Menon; M. Dinesh; Russell Kabir (Mental Illness)
Objectives. Parenting is the general child-rearing practice that has both long- and short-term impacts on the physical, emotional, mental, and social development of the children. We aims at seeing the relationship between parenting style and suicidal behaviors. Methods. A search was conducted in Medline, Embase, and PsychINFO to identify the articles assessing the relationship between different types of parenting styles and suicidal behavior. We included 32 articles in the review published from inception to search date. Results. Among the 32 studies, 27 studies used a cross-sectional study design, 17 were published between 2011 and 2020, and most of the studies included respondents with ages between 9 and 21 years. A wide variety of the used instruments to assess suicidal behavior, and parenting style was noted. Eight studies revealed that authoritarian parenting style is one of the predictors of suicidal behavior, while one study reported the authoritarian parenting style as a resilient factor. Both dominating and flexible parenting styles were associated with higher suicidal behavior, and two studies reported that the permissive style is a contributing factor to suicidal ideation among participants. Conclusion. This review identified the supportive notion that authoritarian parenting style has an association with suicidal behavior in adolescence, and later life. However, a prudential judgment is warranted due to the heterogeneity of study methods, population, contexts, and measurement tools.